2020
DOI: 10.1105/tpc.20.00283
|View full text |Cite
|
Sign up to set email alerts
|

SAUR17 and SAUR50 Differentially Regulate PP2C-D1 during Apical Hook Development and Cotyledon Opening in Arabidopsis

Abstract: One-sentence summary: SAUR17 is highly expressed in apical hooks and cotyledons in the dark, where it promotes etiolation by protecting the phosphatase activity of PP2C-D1 against cell-expansion-inducing SAURs such as SAUR50.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 59 publications
1
67
0
Order By: Relevance
“…S7). A recent study found that SAUR17 has a high affinity for PP2C.D1 without inhibiting its activity ( 52 ). This allows SAUR17 to shield PP2C.D1 from inhibition caused by other SAUR proteins and could serve to reinforce the PP2C.D1-mediated H + -ATPase inhibition resulting from localized phosphatase expression.…”
Section: Resultsmentioning
confidence: 99%
“…S7). A recent study found that SAUR17 has a high affinity for PP2C.D1 without inhibiting its activity ( 52 ). This allows SAUR17 to shield PP2C.D1 from inhibition caused by other SAUR proteins and could serve to reinforce the PP2C.D1-mediated H + -ATPase inhibition resulting from localized phosphatase expression.…”
Section: Resultsmentioning
confidence: 99%
“…The mutant of transcript CL431.Contig8_Ib, which is homologous to E3 ubiquitin-protein ligase DIS1, was defective in trichome cell expansion and actin organization, resulting in a distorted trichome phenotype [ 48 ] in Arabidopsis. Transcript CL11749.Contig1_Ib, defined as a SAUR family protein, plays a central role in auxin-induced acid growth [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, whereas the levels of overexpression of PP2C.D1 in PP2C.D1-GFP were enough to induce a short hypocotyl, they did not promote exaggerated apical hook, suggesting that necessary partners for PP2C.D1 function in hook formation might be limitant, or that the levels of PP2C.D1 in our overexpressing lines were not enough to elicit a hook phenotype. In favor of these latter possibility, a recent paper by Wang et al (2020) reports PP2C.D1 overexpressor lines that have a more closed apical hook in the dark. Although our data do not allow us to conclude that PP2C.D1 function in hook formation involves regulation of ethylene biosynthesis, our results suggest a possible connection between PP2C.D1 activity and ethylene physiology that has not been previously recognized.…”
Section: Discussionmentioning
confidence: 99%